Development of Sour Flavored Noni Juice Using Lactic Acid Compound as a Fermentation Media and Optimation - Jakfar*, Jakfar; Husin, Husni; Nasution, Fahrizal; Ahmadi, Ahmadi (Aceh International Journal of Science and Technology, 2023)
Conventional noni juice production was placing ripe noni fruits into a juice collection vessel for two months or longer. During this time, the noni juice separates (drips) gradually from the pulp. Recent studies have shown that acid catalysts have advantages over conventional noni juice production. This method uses a lactic acid catalyst for the fermentation of noni fruit. The focus of this research is to optimize the effects of various concentrates of Aceh noni X1 (1020 ml), lactose from UHT (ultra-high temperature) milk, and Yakult as a source of Lactobacillus casei X2 (1025 ml) and X3 (2.510 ml). The response variables used were lactic acid levels (Y1, %) and protein levels (Y2, %). The influence of the three individual variables X1, X2, and X3 on the response variables Y1 and Y2 is significant at the 95% confidence level (0.05), but the interaction effect is not significant. Optimal conditions are carried out at the maximum design limits X1, minimum X2, minimum X3, maximum Y1, and maximum Y2 according to the consideration of material prices, and optimal conditions are achieved at each X1 = 20 ml, X2 = 10 ml, X3 = 15.26 ml, Y1 = 1.23% and Y2 = 2.31%, and desirability of 0.92. The lactic acid compound was a fermentation medium for the noni juice-making media. Thus, lactic acid can be believed to be a potentially promising catalyst for producing noni juice while providing economic opportunities and adding value to the noni plant industry.